2021
DOI: 10.29312/remexca.v12i2.2232
|View full text |Cite
|
Sign up to set email alerts
|

Rendimiento, calidad y comportamiento poscosecha de frutos de aguacate ‘Hass’ de huertos con diferente fertilización

Abstract: En frutales, la productividad difiere entre huertos debido a la condición particular del estatus nutrimental de los árboles, fertilidad del suelo, portainjerto, sanidad del cultivo y manejo agronómico. El objetivo de esta investigación fue comparar el rendimiento, calidad y comportamiento poscosecha de frutos de aguacate ‘Hass’ en dos huertos con diferente manejo de la fertilización. El primero se ubicó en Valle de Bravo y el segundo en Villa de Allende, Estado de México. La evaluación se realizó en 2017. En c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…A direct relationship has been reported between the nutritional status of avocado trees and the mineral availability in soils. Some characteristics, such as acidic pH, low levels of OM and high levels of Cu, Fe, K, Ca, B and Zn, lead to a foliar nutritional imbalance [5,7,45]. The Andic soil is a group with a high specific surface area in clay minerals and reactive sites for phosphate retention by non-crystalline aluminum and iron materials [46,47].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A direct relationship has been reported between the nutritional status of avocado trees and the mineral availability in soils. Some characteristics, such as acidic pH, low levels of OM and high levels of Cu, Fe, K, Ca, B and Zn, lead to a foliar nutritional imbalance [5,7,45]. The Andic soil is a group with a high specific surface area in clay minerals and reactive sites for phosphate retention by non-crystalline aluminum and iron materials [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted on Hass avocados in Mexico have shown that the available mineral nutrients in the soil are related to the nutritional status of the trees [5]. In soils with acidic pH and low organic matter content, the concentrations of N, P and Ca were low in leaf tissue, while elements such as Fe and Zn were found in high concentrations [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fruit firmness reached a value similar to that (around 1 N) reported by Cho et al [38] after 8 days of storage; on the other hand, the soluble solids obtained a similar value to that (9.50 • Brix) reported by El-Moniem et al [39] in avocado fruit harvest from an orchard treated with drip irrigation. It was observed that the combined treatment showed the highest values of firmness and soluble solids; this might be related to the optimization of fertilization by the fertigation system, especially the effect of Ca, an element that was highlighted in the combined treatment, and the enhancement of plant nutrition produced by the microorganisms, which would influence both parameters [37,40].…”
Section: Fruit Traits and Yieldmentioning
confidence: 96%
“…This increase in yield was associated with the fact that the practices also enhanced the number of fruits per plant; therefore, the total yield was also increased. This increment in fruit number may be related to a better fruit set due to the precise fertilization and the nutrient absorption improvement [37].…”
Section: Fruit Traits and Yieldmentioning
confidence: 99%